Mobility of Chromium, Copper and Arsenic in Amended Chromated Copper Arsenate Contaminated Soils - Kiwanuka Nakiguli, Caroline; Ojok, Walter; Omara, Timothy; Wasswa, John; Ntambi, Emmanuel (Asian Journal of Applied Chemistry Research, 2020)
The use of copper-based preservatives such as chromated copper arsenate (CCA) and creosote to prolong the life of lumber present environmental concerns because they contain heavy metals and polycyclic aromatic hydrocarbons which are toxic to humans. The aim of this study was to investigate the effects of sewage sludge biosolid amendment on the distribution and mobility of chromium, copper and arsenic in chromated copper arsenate contaminated soils subjected to phytoremediation using maize (Zea mays L.). Place and Duration of the Study: Random composite soil samples from Kitetika wood factory, Wakiso, Uganda and sewage sludge biosolid from National Water and Sewerage Corporation plant in Bugolobi, Kampala, Uganda were collected and prepared. Maize grains were obtained from FICA Seeds Limited (Uganda). The pot experiments and analysis of samples were done at Mbarara University of Science and Technology (Mbarara) and Directorate of Government Analytical Laboratory, Kampala (Uganda), respectively. Methodology: The fresh CCA contaminated soils and sewage sludge biosolid were analyzed for physicochemical parameters and heavy metals (chromium, copper and arsenic). Sewage sludge biosolid was added to 1 kg of the contaminated soils at 5-25% (w/w) in 2 L plastic containers, watered and maintained at 25 ℃ for 14 days to stabilize. Controls were set up with unamended soils. Thereafter, maize was planted in the potted soils for 40 days. The concentrations of the trace metals in the soils were determined after 20 and 40 days of maize growth by atomic absorption spectroscopy. Results: The concentrations of chromium, copper and arsenic in fresh CCA contaminated soils were 365.8 ± 6.18 mg/kg, 109.72 ± 14.04 mg/kg and 28.22 ± 3.8 mg/kg, respectively. Basing on mobility factor, bioavailability of the trace metals followed the chemical sequence copper (8.9%) < chromium (17.1%) < arsenic (30.2%). Conclusion: The maize variety experimented could be used to phytoextract or phytostabilize the trace metals in the CCA contaminated soils without or with 5-25% amendment. Amendment with sewage sludge biosolid improved the phytoremediation potential of maize. Arsenic was the most mobile and bioavailable metal in CCA contaminated soils. Further studies should use other local maize varieties such as Longe series.
Keywords: Heavy metals; Mobility factor; Phytoremediation; Sequential extraction; Sewage sludge biosolid; Wakiso district